2011
DOI: 10.1002/asl.356
|View full text |Cite
|
Sign up to set email alerts
|

Cold European winters: interplay between the NAO and the East Atlantic mode

Abstract: Western Europe has experienced a sequence of unusually cold winters culminating in December 2010, which was the coldest December in the United Kingdom for over 100 years. The North Atlantic Oscillation (NAO) is the most important indicator of the climate of the North Atlantic and Western Europe. However, in this article, we argue that the record cold temperatures in December 2010 cannot be explained by appeal to the NAO alone. Rather we show that the consideration of another atmospheric teleconnection pattern,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 41 publications
8
90
0
3
Order By: Relevance
“…Importantly, our EA and SCA indices are of opposite sign to those presented in Moore et al (2013); the reader is referred to their figure 2 in contrast with our Figure 2). However, our EA and SCA indices are consistent with others (Wallace and Gutzler, 1981;Moore and Renfrew, 2012; see section S2 of the Supporting Information), and they also yield their expected climatic effects (CPC, 2012). This has important implications because the NAO dipole movements associated with NAO-EA and NAO-SCA combinations suggested by Moore et al (2013) appear to be reversed, and are the opposite of those inferred in this study.…”
Section: Teleconnection Indicessupporting
confidence: 89%
See 2 more Smart Citations
“…Importantly, our EA and SCA indices are of opposite sign to those presented in Moore et al (2013); the reader is referred to their figure 2 in contrast with our Figure 2). However, our EA and SCA indices are consistent with others (Wallace and Gutzler, 1981;Moore and Renfrew, 2012; see section S2 of the Supporting Information), and they also yield their expected climatic effects (CPC, 2012). This has important implications because the NAO dipole movements associated with NAO-EA and NAO-SCA combinations suggested by Moore et al (2013) appear to be reversed, and are the opposite of those inferred in this study.…”
Section: Teleconnection Indicessupporting
confidence: 89%
“…The spatial non-stationarity of the regional NAOclimate relationships described in section 3.2 can be rationalized on the basis of recent studies of SLP patterns (Moore and Renfrew, 2012) that demonstrated shifts in the NAO centres of actions relative to those used to define the classic station based NAO indices (Hurrell, 1995;Jones et al, 1997) linked to the coexisting states of the EA and the SCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear the reason for this discrepancy. However, it may be related to lowfrequency variability in the location and depth of the Iceland Low and/or the Lofotes Low (Hilmer and Jung, 2000;Jahnke-Bornemann and Bruemmer, 2009;Moore et al, 2011;Moore and Renfrew, 2012). As can be seen from Figure 8, such changes can impact icing rates in the Greenland Sea.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is characterised by an anomaly in the north-eastern North Atlantic Ocean, between the NAO centres of action. Negative values mean a southward displacement of the NAO centres of action and lower temperatures (Moore and Renfrew 2012), positive values correspond to more zonal winds over Europe and expected higher temperatures. The third dominant mode is the Scandinavian pattern, also called the Eurasian (Wallace and Gutzler 1981) or blocking pattern (Hurrell and Deser 2009), which in its positive phase is characterised by a high-pressure anomaly over Scandinavia and a lowpressure anomaly over Greenland.…”
Section: Box 41 North Atlantic Oscillationmentioning
confidence: 99%